Protective Effect of Cow Urine Distillate in Streptozotocin Induced Type I Diabetes in Rats - Mahida, Nishtha R.; Mandali, G.C.; Raval, S.K.; Joshi, B. P. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The sacred Indian cow, Bos indicus known as “Kamadhenu” in Indian scripts, is believed to be a “mobile hospital” for the treatment of many diseases. Although Indian Ayurvedic literature cites many medicinal properties of cow urine, there is no scientific evidence to support this. Hence, this study was undertaken to validate antidiabetic property of cow urine. The effect of cow urine distillate was studied in vivo in induced diabetic rats. Diabetes was induced by administration of single injection of streptozotocin (60 mg/kg b.wt.) intraperitoneally. The antidiabetic effect of cow urine distillate in two different doses (5.0 ml and 10.0 ml/kg b.wt.) was studied in these adult diabetic rats. The cow urine distillate was administered orally to the experimental rats from 8th day and continued for 42 days thereafter. The assessment included fasting blood glucose levels, serum lipid profiles and body weight changes. The cow urine distillate produced a significant (P
Keywords: Diabetes mellitus; Cow urine distillate; Streptozotocin; Blood glucose; Lipid profile